Developing Creativity Through Dance Creation in the Musical Drama Mataram Harmoni at SMPN 9 Mataram - Ni Luh Ayu Srihandayani; Duwi Purwati; Wahyu Kurnia; Beny Permana; Lalu Dwi Satria Ardiansyah (International Journal of Social Sciences and Humanities, 2023)
This research aims to: (1) determine the stages of the process of developing student creativity through dance creations in the musical drama performance Mataram Harmoni at SMPN 9 Mataram; and (2) understand the role of schools in increasing student creativity through the art of dance. The research uses a case study method with data collection techniques in the form of observation, interviews, documentation and questionnaires. Data analysis was carried out qualitatively through data reduction, presentation and verification. The research results show that the dance creation process involves stages of observation, exploration, execution and evaluation, as well as physical exercise to develop students' focus and imagination. Creativity indicators such as curiosity, self-confidence, perseverance, independence, imagination and courage are achieved well. Schools play an active role through providing facilities, coordinating and promoting activities. Research recorded an 86% increase in student creativity, showing that this process is effective in developing artistic skills, character and collaboration, while maintaining cultural values.